Financial flows management based on logistic budgeting (Economics and region, 2019)
There is considers the problem of increase of system effectiveness of management of financial flows in logistics systems. The necessity of introduction of the system of logistics budgeting at industrial enterprises is substantiated. The advantages and disadvantages of the use of logistics budgeting are determined.
Keywords: financial flows; financial flows management; logistic budgeting; budgeting in logistic systems